Fabrication of silver-chitosan nanocomposite films and their antibacterial activity. Issue 1 (June 2020) - Susilowati, E; Maryani,; Ashadi,; Marwan,
Abstract: The silver-chitosan nanocomposite film fabrication was carried out by the preparation of silver nanoparticles using chemical reduction methods assisted with microwave irradiation with chitosan as a reducing agent as well as a stabilizer. Silver nitrate is used as a precursor and NaOH as an accelerator. Silver-chitosan nanocomposite colloids were converted into films by casting techniques at the room temperature. Based on UV-Visible spectra, colloidal nanocomposites show absorption peak at the range of 409-412 nm. Based on TEM images, the silver nanoparticles are spherical shaped and distributed with a diameter of 6-10 nm. Based on FTIR spectra, interactions between silver nanoparticles and chitosan occur in the hydroxyl group (-OH) and amine group (-NH) of the chitosan polymer chain. Based on SEM images, the silver-chitosan nanocomposite films show a compact but rough surface morphology. The increase in tensile strength and decrease in elongation at break of the film was in line with the increase in the concentration of silver nitrate, while the value of the elasticity of the film fluctuates depending on the tensile strength and elongation at break. The increasing concentration of silver nitrate also causes an increase in the degree of swelling. silver-chitosan nanocomposite films showed better antibacterial activity against Escherichia coli than Staphylococcus aureus.